2003
DOI: 10.1167/iovs.02-0478
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fas-FasL in the Development and Treatment of Ischemic Retinopathy

Abstract: Fas-FasL interactions regulate the extent of oxygen-induced retinal neovascularization. The inhibition of neovascularization in B6 gld, and B6-lpr mice by PEDF suggests that Fas-FasL interactions are probably not the mechanism for inhibition in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Several pathways have been suggested to explain the antiangiogenic activity of PEDF, such as inducing EC death by activating the Fas/FasL death pathway (31). However, PEDF still inhibits neovascularization in mice lacking either Fas or FasL (54), implying that either other pathways are involved or that PEDF does not use Fas-FasL interactions to inhibit retinal neovascularization. Following this hypothesis, other groups have reported that MAPK JNK and p38 influence EC apoptosis by modulating c-FLIP or caspase activity (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways have been suggested to explain the antiangiogenic activity of PEDF, such as inducing EC death by activating the Fas/FasL death pathway (31). However, PEDF still inhibits neovascularization in mice lacking either Fas or FasL (54), implying that either other pathways are involved or that PEDF does not use Fas-FasL interactions to inhibit retinal neovascularization. Following this hypothesis, other groups have reported that MAPK JNK and p38 influence EC apoptosis by modulating c-FLIP or caspase activity (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The gld and lpr mutations were bred onto the BALB/c background by crossing B6-gld and B6-lpr (originally obtained from The Jackson Laboratory) to BALB/c for a minimum of 10 generations. Mice were screened by PCR as described (20). Because the mutations were derived from B6 mice, these strains are designated C.B6-lpr and C.B6-gld.…”
Section: Micementioning
confidence: 99%
“…The gld and lpr mutations were bred onto the BALB/c background by crossing B6-gld and B6-lpr (originally obtained from The Jackson Labortory, Bar Harbor, ME) to BALB/c for a minimum of 10 generations. Mice were screened by PCR as described (28). Since the mutations were derived from B6 mice these strains are designated C.B6-lpr and C.B6-gld.…”
Section: Micementioning
confidence: 99%